MAKING GEOGRAPHICAL NAMES CONDITIONS AND REASONS - Kalandar Saparov; Anvar Rasulov; Asror Nizamov (Scholar Express Journal, 2021)
Toponymy plays an important role in the study of many disciplines such as geography, history, literature, biology, geology, ethnography. It was formed a little later as a science, that is, although relatively young, in our time it has been formed as one of the main methods of studying the above-mentioned subjects. Because in each of them, knowing is done through names. Without it, it is difficult to distinguish geographical names from each other, and naturally leads to a mixture of concepts of each category (city, village, mountain, desert, plant, animal).
Keywords: Geography; place names; grouping; zoning